Chewie and the porgs - Shinick, Kevin, 1969- (Disney, Lucasfilm Press, 2017)
When Chewbacca and Rey travel to an island on the planet Ahch-To in search of Luke Skywalker, they meet the porgs, who must learn to share their island with the Wookie.